GENDER FEATURES OF JURIDICAL RHETORIC - Khujaniyazova Hilola Turayevna (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the gender features of Juridical rhetoric from a comparative and pragma linguistic perspective. The study analyzes the rhetorical and communicative characteristics of male and female Juridical professionals in courtroom discourse, focusing on the speech of judges, advocates, and prosecutors in Uzbek and English Juridical practice. Particular attention is paid to lexical choice, grammatical structures, prosodic features, emotional-evaluative elements, and argumentative strategies employed in Juridical communication. The research also explores the influence of national mentality, cultural values, and institutional traditions on Juridical discourse.